Synthesis and Characterization of Lead-Cadmium Selenide Nanoparticles by Polyol Method for Semiconductor based Applications - Karthika*, P.C.; Ratnakar, A.; Balasubramaniam, N.; Sahatiya, Parikshit; Teja, Krishna; Ajit Mohan, Arjun (Asian Journal of Chemistry, 2013)
Lead-cadmium selenide nanoparticles were synthesized using magnetic stirrer assisted polyol method using cadmium acetate, lead acetate and selenium powder. The obtained resultant product was found to have a cubic structure from the XRD data analysis and UV-visible spectrum, scanning electron microscopic pictures showed that lead and cadmium selenide particles of smaller than 60 and 150 nm showed that the product have a good band gap of 3.1 eV making it a good semiconducting material. While comparing the result with cadmium selenide nanoparticles it was found that lead-cadmium selenide is a little enhanced than the former with respect to semiconducting property and semiconductor based electronics applications.